(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article highlights the importance, possibilities and effectiveness of using modern computer programs in speech therapy. Digital technologies help to organize correctional classes with children with speech disorders in a more interesting, interactive and demonstrative way.